Comprehensive Study of Jewish English and Its Features in the Modern-Day English-Speaking World - Поворозник, Назар Ігорович (Київський національний університет імені Тараса Шевченка, 2025)
This Bachelor’s Thesis explores the grammatical, lexical, and phonetic peculiarities of Jewish English found in 4 episodes of the Netflix miniseries Unorthodox. The study focuses on the community of Hasidic JE speakers, whose speech, as proposed by M. Newman, tends to be most notably influenced by Yiddish and Textual Hebrew, in Williamsburg, New York City. Six speakers were chosen for analysis on the presence or absence of the features described in the hypothesis. Chapter I defines the concept of Jewish English, tracing its emergence and development within the United States, and examines the sociolinguistic conditions that have shaped its evolution. It presents a range of definitions, explores its key grammatical, lexical, and phonetic features, and discusses how these vary among Jewish communities depending on degrees of ethno-religious affiliation. Particular attention is given to the sociocultural variables that influence the manifestation of Jewish English features, with secular speakers showing fewer linguistic markers and Hasidic speakers exhibiting more distinct usage. Chapter II offers a qualitative analysis of Jewish English as portrayed in the Netflix miniseries Unorthodox, focusing on the occurrence and function of specific linguistic features. Lexical analysis revealed extensive Yiddish influence, including religious terminology, kinship terms, culinary vocabulary, and idiomatic expressions in both in-group and out-group communication. Grammatical analysis indicated limited influence, with few nonstandard structures present, while phonetic analysis highlighted notable features such as the voiced glottal fricative /ɦ/ replacing the standard English /h/. Together, the findings underscore the persistence and visibility of Jewish English features within media representations of Hasidic communities. The study applies a qualitative approach of corpus data, based on the foregoing miniseries. By analyzing the grammatical, lexical, and phonetic features found in the segments and their correlation with in-group and out-group communication, it demonstrates how important one’s ethno-religious identity might be, especially in the variety language analysis of a community.

У цій бакалаврській роботі досліджуються граматичні, лексичні та фонетичні особливості єврейського варіанту англійської мови (Jewish English), виявлені у чотирьох епізодах міні серіалу “Unorthodox” (“Неортодоксальна”) від платформи Netflix. Дослідження зосереджено на спільноті хасидських носіїв єврейського варіанту англійської, мова яких, за припущенням М. Ньюмана, зазнає найбільшого впливу їдишу та текстуального івриту, у районі Вільямсбург, Нью-Йорк. Для аналізу були обрані шість мовців, з метою виявлення наявності або відсутності лінгвістичних рис, описаних у гіпотезі. У першому розділі подається визначення поняття єврейського англійського варіанту, простежується його виникнення та розвиток у США, а також розглядаються соціолінгвістичні чинники, що вплинули на його еволюцію. Розділ містить огляд різних визначень цього терміну, описує основні граматичні, лексичні та фонетичні характеристики, а також аналізує варіативність цих ознак серед різних єврейських спільнот залежно від ступеня етнорелігійної ідентичності. Особливу увагу приділено соціокультурним змінним, які впливають на вираження мовних особливостей: світські носії виявляють менше характерних рис, тоді як хасидські — демонструють їх більш виразно. Другий розділ містить якісний аналіз єврейського варіанту англійської, представленого в міні серіалі Unorthodox, з фокусом на функціонування та поширеність окремих лінгвістичних явищ. Лексичний аналіз виявив значний вплив їдишу, зокрема в релігійній лексиці, термінах родинних зв’язків, кулінарній лексиці та ідіоматичних виразах, що вживаються як у внутрішньогруповому, так і в зовнішньогруповому спілкуванні. Граматичний аналіз виявив обмежений вплив, оскільки нестандартні структури зустрічалися рідко. Фонетичний аналіз, своєю чергою, засвідчив наявність таких характерних ознак, як заміна глухого гортанного фрикативного [h] на дзвінкий [ɦ]. Дослідження спирається на якісний підхід до аналізу корпусних даних, отриманих із вказаного міні серіалу. Аналіз граматичних, лексичних та фонетичних особливостей, а також їх зв’язку з внутрішньогруповою та зовнішньогруповою комунікацією демонструє важливість етнорелігійної ідентичності для вивчення мовної варіації у межах окремої спільноти.
Keywords: Jewish English; religiolect; variety; ethno-religious identity; language community; Eastern-Ashkenazic English; Hasidic community; єврейська англійська; релігіолект; діалект; етно-релігійна ідентичність; мовна спільнота; східно-ашкеназька (ашкеназійська) англійська; хасидська спільнота